PENGARUH MODEL COOPERATIVE CLASS EXPERIMENT (CCE) TIPE TEAM GAMES TOURNAMENT (TGT) PADA KBK DAN HASIL BELAJAR SISWA - -, Supartono; -, Latifah; Sa’idun, Fajar Mahda Akhmad (Universitas Negeri Semarang, 2013)
Learning with the conventional method make competency achievement in chemistry subject is still low. This study aimed to determine the effect of Model Cooperative Class Experiment (CCE) type Team Games Tournament (TGT) on CBC and Learning Outcomes on high school students in the topic of redox reactions. Sample determination was using cluster random sampling technique, class X8 grade students is as the experimental class and X7 class is as control class. The method used in data collection is documentation, in the form of multiple choice test and an essay in the form of open-ended questions and observations. The results showed that analysis of CBC data test achieved fifth subindikator CBC in the experimental class gained an average of 73.75%, which means that students can develop CBC with good criterion, while the control class with an average of 64.68% in the CBC is sufficient criteria. The analysis data obtained rb 0.51 with the contribution of 26.29%. The results of this study concluded that the implementation of Cooperative Learning Model Class Experi ment (CCE) Study Team Games Tournament (TGT) type have signiffican effect on CBC and student learning outcomes in high school in Semarang on the redox subject with the contribution of 26.29%.